THE USE OF ELECTROSPUN IRON OXIDE NANOFIBERS IN COATING FROZEN BEEFBURGER - Majd A. A.; Alrubeii, A. M. S.; L. T. Al–Hadedee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted on the in coating of beef burger using electrospun iron oxide nanofibers at two concentrations6, 8 % , to improve the chemical and physical properties of the beef burger during a 3-month frozen storage period. The results of the study showed that the addition of electrospun nanofibers contributed to reducing the total bacterial count, as well as the count of psychrophilic bacteria and coliform bacteria, to 4.88* 103, 4.62* 103, and 3.15* 101, 3.64 *101, respectively, and 2.15* 103, 2.49* 103 colony-forming units (CFU/g) respectively, during the final storage period. The moisture, protein, fat, and ash percentages in the frozen beef burger were found to be 60.12%, 19.09%, 19.31%, and 1.28%, respectively. The addition of iron oxide nanofibers also improved the water holding capacity of the frozen beef burger, with values of 49.16% and 39.69%, respectively. Furthermore, the pH values remained constant at 5.68 and 5.63, respectively, during the final storage period. The addition of nanofibers also reduced the peroxide value to 6.77 and 6.62 milliequivalents per kilogram, respectively, during the final storage period.The aim of this study was to investigate the effects of adding electrospun nanofibers to biopolymers used in beef burger on their qualitative properties.